2015
DOI: 10.1097/aln.0000000000000596
|View full text |Cite
|
Sign up to set email alerts
|

Health Implications of Disrupted Circadian Rhythms and the Potential for Daylight as Therapy

Abstract: This paper reviews the molecular basis of circadian rhythms and the pathophysiologic consequences of alterations in these rhythms, and explores the concept of daylight as therapy to restore disrupted circadian rhythms and improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 28 publications
4
55
0
1
Order By: Relevance
“…Biological systems in all organisms had to adapt to sunlight cycles and oxygen saturation to survive. As a result, almost all organisms on this planet are equipped with light and oxygen sensing proteins [4, 5]. Light sensing proteins are known as circadian rhythm proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Biological systems in all organisms had to adapt to sunlight cycles and oxygen saturation to survive. As a result, almost all organisms on this planet are equipped with light and oxygen sensing proteins [4, 5]. Light sensing proteins are known as circadian rhythm proteins.…”
Section: Introductionmentioning
confidence: 99%
“…during sepsis, heart ischemia or lung disease), the need to monitor light or to treat disrupted circadian rhythms has not been introduced into clinical practice yet. During the last few years, groundbreaking research has revealed a multitude of circadian genes affecting a variety of clinical diseases, including diabetes, obesity, sepsis, cardiac ischemia, and sudden cardiac death (2, 4, 5). Interestingly, the ICU environment in particular has been shown to disrupt the circadian system of patients (2).…”
mentioning
confidence: 99%
“…Future analysis of different light conditions in different settings seems mandatory to understand the impact on health and well-being. Future research will hopefully guide us how to use light a therapy (2, 4, 5). …”
mentioning
confidence: 99%
See 2 more Smart Citations